Penerapan model pembelajaran discovery learning untuk meningkatkan keterampilan berpikir kreatif dalam pembelajaran IPS pada peserta didik kelas V sekolah dasar - Rafli Arga Prasetya (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
Abstract. The goal of this research is to increase creative thinking skills in social science learning by applying Discovery Learning model. This study is Classroom Action Research and  have two cycles. The subjects of this study were students of the 5th students at SD Negeri 01 Papahan Karanganyar in the 2019/2020 academic year, totalling 24 students. This study uses data collection techniques in the form of interview, observation, and tests, with data analysis of content validity and triangulation. 42% of classical completeness is obtained in the 1st cycle,      and the research continued in the 2nd cycle with a result of 81% in classical completeness. Based on the result of the study, it can be concluded that the creative thinking skills in social science learning on 5th students of SD Negeri 01 Papahan karanganyar in the 2019/2020 academic year can be improved through the Discovery Learning  model. This research is expected to make teachers more skilled in applying the Dicsovery Learning model to improve student’s creative thinking skills. Keywords: creative thinking skills, social science learning, discovery learning model, elementary school